2010
DOI: 10.4317/medoral.15.e755
|View full text |Cite
|
Sign up to set email alerts
|

Distal probing depth and attachment level of lower second molars following surgical extraction of lower third molars: A literature review

Abstract: A review of the literature is made to evaluate factors that influence probing depth and attachment level on the distal aspect of the lower second molar (L2M) following extraction of a lower third molar (L3M). The PubMed database was searched for studies published between 1997 and March 2009 using the following keywords: mandibular third molar, distal periodontal defect, distal probing depth, distal attachment level, flap design. Randomized prospective studies, with a minimum follow-up of three months for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…Nevertheless, results of these studies advocated the fact that selection of flap design does not seem to have a significant effect on the health of M2M periodontal tissues. These conclusions were in agreement with those of the overviews conducted by Karaca et al 15 and Aloy‐Prosper et al 13 Contrary to the findings of Buti et al, 47 Ramírez et al 18 in their review found insufficient evidence to recommend the use of mechanical debridement of second molars after the extraction of third molars. Aloy‐Prosper et al 13 in their review concluded that curettage of the distal radicular surface of the M2M, together with oral hygiene control, reduced PD values.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Nevertheless, results of these studies advocated the fact that selection of flap design does not seem to have a significant effect on the health of M2M periodontal tissues. These conclusions were in agreement with those of the overviews conducted by Karaca et al 15 and Aloy‐Prosper et al 13 Contrary to the findings of Buti et al, 47 Ramírez et al 18 in their review found insufficient evidence to recommend the use of mechanical debridement of second molars after the extraction of third molars. Aloy‐Prosper et al 13 in their review concluded that curettage of the distal radicular surface of the M2M, together with oral hygiene control, reduced PD values.…”
Section: Discussionsupporting
confidence: 87%
“…Management of impacted M3M poses another relevant challenge for the clinician because surgical removal of wisdom teeth has been associated with the risk of having persistent or developing new periodontal defects at the distal aspect of the mandibular second molar (M2M) 9–13 . To reduce the risk of developing periodontal defects, different treatment strategies have been proposed, consisting of adjunctive systematic debridement of M2M distal root surface, specific access flap designs, soft‐tissue suturing, regenerative procedures, and bone grafting techniques, for their potential benefits in periodontal healing distally to M2M compared to conventional M3Ms extractions 2 , 14 , 15 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility to concentrate growth factors in a surgical wound seems to allow activation of cellular events, providing a final gain in quality and time of healing. The use of PRP has been shown to be a useful tool in aiding periodontal and bone regeneration in vivo because of the high content of growth factors [16]. Results showed that PRGF contains a pool of growth factors that significantly stimulated the proliferation of tenocytes and induced the paracrine secretion of both VEGF and HGF.…”
Section: Discussionmentioning
confidence: 83%
“…Some investigators have reported significant improvements in tissue healing and bone formation using PRP [1,4,7,8,11,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] whereas others did not observe improvements [2,5,13,14,[32][33][34][35][36]. Some have given no conclusion regarding effect of PRP application in maxillofacial region than periodontal defects [37].…”
Section: Discussionmentioning
confidence: 99%